2011
DOI: 10.1093/neuonc/nor074
|View full text |Cite
|
Sign up to set email alerts
|

Neurocytomas: Long-term experience of a single institution

Abstract: There is a lack of studies reporting on outcomes of control and treatment toxicities for neurocytomas. A 25-year retrospective review of a tertiary center's experience with neurocytomas was completed to report on these outcomes. All cerebral neurocytoma cases (19 patients; median age, 31 years; range, 18-62 years; 18 intraventricular and 1 extraventricular) treated between 1984 and 2009 were analyzed, including central pathology and radiology reviews. Median follow-up was 104.5 months (range, 0.75-261.7 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 33 publications
3
41
0
5
Order By: Relevance
“…As CNs have a deep-seated intraventricular location, an abundant blood supply, and proximity to critical structures such as the fornix and thalamus, the surgical morbidity and mortality rates were relative high (6,8,(10)(11)(12)(13)(14)19,23). some reported rates of GTR ranged from 31% to 88%, mortality rates varied between 0% and 19%, and morbidity rates varied between 16% and 52% (Table IV).…”
Section: Surgical Strategymentioning
confidence: 99%
“…As CNs have a deep-seated intraventricular location, an abundant blood supply, and proximity to critical structures such as the fornix and thalamus, the surgical morbidity and mortality rates were relative high (6,8,(10)(11)(12)(13)(14)19,23). some reported rates of GTR ranged from 31% to 88%, mortality rates varied between 0% and 19%, and morbidity rates varied between 16% and 52% (Table IV).…”
Section: Surgical Strategymentioning
confidence: 99%
“…Interestingly, in our series, greater extent of initial resection and smaller initial tumor size did not appear to correlate with improved local control. While most prior case series [18, 29, 32] assert that incomplete resection is associated with increased recurrence, this finding is inconsistent. A recent retrospective study of 45 central neurocytoma patients reported no significant difference in local control or survival between GTR and STR, but found local control and survival advantages in patients with lower mitotic indices [17].…”
Section: Discussionmentioning
confidence: 97%
“…Surgical resection is the primary treatment to establish pathologic diagnosis, to clear CSF pathways and to address any obstructive hydrocephalus [5]. Most studies support the idea that complete resection is an important predictor of recurrence [16, 18, 20, 21]; however, this fact remains unclear since other reports have not identified significant improvements in survival or local control [10, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Four patients exhibited features of histological atypia by pathological analysis, including necrosis and vascular hypertrophy. This indicated that in EVNs, the presence of a 1p19q codeletion, although rare, may imply aggressive clinical behavior and a poorer outcome (46). Mutation of the isocitrate dehydrogenase enzyme isoform 1 (IDH1 R132) and 2 (IDH2 R172) is associated with a large proportion of diffuse astrocytic and oligodendroglial tumors.…”
Section: Discussionmentioning
confidence: 99%